2019
DOI: 10.1002/jcu.22787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of early‐diastolic tissue velocity imaging of lateral mitral annulus for prognosis of nonischemic left ventricular dysfunction

Abstract: Purpose We explored the potential of tissue velocity imaging (TVI) for prognosis of nonischemic left ventricular (LV) dysfunction (LVD). Methods We reviewed 138 nonischemic LVD patients (58 ± 14 years) who underwent both cardiac magnetic resonance (CMR) and echocardiography. Septal and lateral mitral annular TVI data were compared with late gadolinium enhancement (LGE) on CMR. During a mean follow‐up of 24 months, recovery (>15%) of LV ejection fraction and clinical outcomes (cardiovascular death and heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…erefore, the difference between normal and abnormal is magnified, and the dependence on local changes is less. e average velocity of the various parts of the mitral valve ring in the early diastole can be used as a sensitive indicator to reflect the left ventricular diastolic function, and it will hardly be disturbed by heart rate and load [25,26]. e results of this study showed that the combined use of the TNN model can more accurately identify the Em, especially the E/Em value of patients with atrial fibrillation, which was greatly different from the control group, indicating that the left ventricular diastolic function measured by this method was more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, the difference between normal and abnormal is magnified, and the dependence on local changes is less. e average velocity of the various parts of the mitral valve ring in the early diastole can be used as a sensitive indicator to reflect the left ventricular diastolic function, and it will hardly be disturbed by heart rate and load [25,26]. e results of this study showed that the combined use of the TNN model can more accurately identify the Em, especially the E/Em value of patients with atrial fibrillation, which was greatly different from the control group, indicating that the left ventricular diastolic function measured by this method was more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular filling pressure has proven to be an early marker and predictor of outcomes in cardiovascular diseases assessment and a number of echocardiographic measurements are used to estimate left ventricular pressure parameters [10]. The early lateral annular velocity (E'), the mitral profile (E/A) and the mitral annular early diastolic velocity (E/E') are commonly used for the evaluation of diastolic function by way of non-invasive echocardiographic assessment [11].…”
Section: Introductionmentioning
confidence: 99%